2010
DOI: 10.1007/s10096-010-1054-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus seroprevalence in exposed and unexposed populations of hospital employees

Abstract: The objective of this work was to compare the seroprevalence of cytomegalovirus in an unexposed and exposed population, both working in a hospital, and to study the occupational risk factors related to seropositivity, while taking personal risk factors into account. We conducted a cross-sectional study in a French hospital over a period of 12 months. The overall seroprevalence among the 550 subjects was 49.5%. The multivariate analysis showed that seropositivity was significantly associated with age (36-43 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…Our findings reinforced prevalence results found in previous surveys conducted in France, targeted at specific sub-populations such as pregnant women or healthcare workers [22–24]. Furthermore, our prevalence estimates were comparable with those obtained in national surveys conducted in the general populations of other Western countries, such as the USA, the Netherlands and Australia [2, 27, 28].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings reinforced prevalence results found in previous surveys conducted in France, targeted at specific sub-populations such as pregnant women or healthcare workers [22–24]. Furthermore, our prevalence estimates were comparable with those obtained in national surveys conducted in the general populations of other Western countries, such as the USA, the Netherlands and Australia [2, 27, 28].…”
Section: Discussionsupporting
confidence: 91%
“…The only exception to this trend was observed in children less than 6 months who had high prevalence (84.4%) reflecting transient presence of transplacentally derived maternal IgG antibodies. Similar results were found in majority other studies [10,15,18,19,33]. Comparing seroprevalence in the similar age groups, some differences were found in children and adolescents.…”
Section: Discussionsupporting
confidence: 91%
“…Prevalence rates are reported to be 41%-92% in children and adolescents [12][13][14][15], 45%-94% in adult general population [14,[16][17][18][19], 30%-91.5% in pregnant women [20][21][22][23][24] and 68%-99% in hemodialysis patients [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies conducted in recent decades have suggested a low CMV risk for staff in children’s hospitals [ 27 ], [ 28 ], [ 29 ], [ 30 ], [ 31 ]. However, Lepage et al [ 32 ] described an increased CMV risk among paediatric care assistants as against employees with no contact with patients. (OR: 1.8; 95% CI 1.1–2.8).…”
Section: Discussionmentioning
confidence: 99%